Sistemas de riego por aspersión subfoliar en el cultivo de cacao (Theobroma cacao L.) - Vargas Acosta, Douglas Edison (2022)
Establishing a subfoliar irrigation system in a cocoa crop is one of the most important agronomic methods, which allows to achieve the greatest agricultural progress of the crop by increasing its potential yield. Taking into account that irrigation application is the incorporation of water to the soil in order to provide the necessary moisture for plant development. Cocoa is a plant that needs a good supply of adequate water to carry out its metabolic activities, being of great importance to establish a subfoliar irrigation system, which allows increasing the efficiency of irrigation to achieve productive and environmental sustainability in areas where irrigation water does not meet the demand. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the subfoliar sprinkler irrigation system in the cultivation of cocoa (Theobroma cacao L). From the above detailed, it was determined that there is a wide application of the subfoliar irrigation system in the cocoa crop, because it has a very high application efficiency (80%), being important to meet the water needs of the cocoa crop. The agronomic design is very important within the subfoliar irrigation system based on the water needs of the plants according to climate, soil type and irrigation performance, as well as the range and time of irrigation desired in each vegetative cycle. The types of sprinklers used in subfoliar irrigation in the cocoa crop are: Smooth Drive Boq # 7 (7/64") Lime, Xcel Wobbler, Xcel-Wobbler Nozzle # 9 Gray (9/64").